Prevalence of undernutrition and its associated factors among orphans aged 6–59 months in Nekemte town, Ethiopia - Werku Etafa; Fayera Abdana; Emebet Bobo; Wandimu Muche Mekonen; Dawit Tesfaye Daka; Meseret Belete Fite; Tesfaye Shibiru; Asefa Negeri; Gutu Leta; Dereje Temesgen (PLoS ONE, 2025)
Background Undernutrition is a leading cause of childhood mortality in low-income countries. Orphaned children are particularly vulnerable due to the absence of parental care and support, as well as factors such as infection and poor feeding practices. Undernutrition is often associated with developmental delays and recurrent infections. This study aimed to determine the prevalence of undernutrition and its associated factors among orphaned children aged 6–59 months in Nekemte town, Ethiopia. Methods This study employed a cross-sectional, community-based study collected data through interviewer-administered questionnaires and anthropometric measurements. A total of 373 orphans paired with caregivers were selected using a simple random sampling technique from first June to July 30, 2023. Data were coded and entered into Epi Data V.4.6, and SPSS version 25 was used for analysis. Anthropometric indices were measured using the WHO ENA Software. Both binary and multivariate logistic regression analyses were conducted with a 95% confidence interval to identify factors associated with undernutrition, considering a significance level of p < 0.05. Results The prevalence of stunting, wasting, and underweight in the studied population was 37.3% (95% CI: 32.4–41.8), 28.7% (95% CI: 23.6–33.2), and 24.4% (95% CI: 20.1–28.9), respectively. Factors associated with stunting included caregivers who obtained the child not through a legal process (AOR = 1.74, 95% CI: 1.06–2.86) and children who did not receive vitamin A in the last six months (AOR = 0.59, 95%CI: 0.371–0.94). For wasting, significant associations were found with orphans aged 6–23 months (AOR = 2.76, 95%CI: 1.27–6.02), those receiving treatment (AOR = 0.45, 95% CI: 0.26–0.76), incomplete vaccination status (AOR = 3.53, 95% CI: 1.65–7.04), and caregivers lacking information about nutrition for children under five (AOR = 1.82, 95%CI: 1.08–3.06). Additionally, orphans who began consuming additional food before six months of age (AOR = 2.76, 95%CI: 1.27–6.02) and those with caregivers who were government employees (AOR = 1.89, 95% CI: 1.07–3.34) were more likely to be underweight. Conclusions The prevalence of undernutrition among orphaned children is high in Nekemte town. It is crucial to improve the knowledge and communication skills of healthcare workers and caregivers regarding infant and young child feeding practices and vitamin A supplementation for children under five years of age. Additionally, improving the supervision of orphans by legal bodies is essential for better health outcomes.